2015
DOI: 10.7324/japs.2015.50714
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Mucoadhesive In Situ Gel of Granisetron Hydrochloride using Natural Polymers

Abstract: The prolonged residence of drug formulation in the nasal cavity is of utmost importance for intranasal delivery of drug. Present investigation was aimed to develop a mucoadhesive in situ gel of Granisetron hydrochloride (GH) with reduced nasal mucocilliary clearance in order to improve the bioavailability of the antiemetic drug, granisetron hydrochloride. The in situ gelation upon contact with nasal mucosa was conferred via the use of the thermogelling Pluronic flake 127 (PF 127). Moringa gum (MG), carboxymeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…TG is composed of (1→4)-β-D-glucan back-bone substituted with side chains of α-D-xylopyranose and β-D-galactopyranosyl(1→2)-α-D-xylopyranose linked (1→6) to glucose residues [20] . It has been used in the development of various drug delivery systems due to its hydrophilic and bioadhesive properties [21][22][23][24][25][26][27] . Although TG shows presence of non-sterically hindered hydroxyl groups, very few reports mentioned the use of pure TG in chemically crosslinked hydrogels [28] .…”
Section: Research Papermentioning
confidence: 99%
“…TG is composed of (1→4)-β-D-glucan back-bone substituted with side chains of α-D-xylopyranose and β-D-galactopyranosyl(1→2)-α-D-xylopyranose linked (1→6) to glucose residues [20] . It has been used in the development of various drug delivery systems due to its hydrophilic and bioadhesive properties [21][22][23][24][25][26][27] . Although TG shows presence of non-sterically hindered hydroxyl groups, very few reports mentioned the use of pure TG in chemically crosslinked hydrogels [28] .…”
Section: Research Papermentioning
confidence: 99%
“…The results also showed that increase in concentration of crosslinking agent decreases the percentage mucoadhesion; the reason may be attributed to less availability of polymer chains for entanglement with the mucus. In vitro drug release study It was observed that formulation C1 shows only 37.18 % at the end of 8 hrs which contains pure drug which indicates drug molecules presenting difficulties in their solubility in dissolution medium [17].It was observed that formulation C5 showed more drug release than formulation C4 and C3, thus it was found from result that with the increasing concentration of DOM solid dispersion in formulation, % drug release also get increased.…”
Section: Mucoadhesion Studymentioning
confidence: 97%
“…The microbeads are more spherical in shape before solid dispersion loading. The drug loading and solid dispersion loading lead to formation of irregular microbeads with rough surface which may provide higher specific surface area [17]. SEM of the surface of sectioned solid dispersion loaded microbeads shows that many large pores are present in the gel matrix may be due to contraction of gel matrix caused by water evaporation is depressed by the presence of carbopol [4].…”
Section: Characterization Of Dom/ Hpmc/ca Solid Dispersion Containingmentioning
confidence: 99%
“…The formulation has the advantage to prevent the anterior leakage of the dosage form and enhance the nasal bioavailability due to longer residence time in the nasal cavity. For better patient compliance, it is desirable to deliver the drug quickly through the nasal mucosa because it is difficult to hold the gel in the nasal cavity for more than 7-8 h. So, we have used the permeation enhancer 4,5,6 .…”
mentioning
confidence: 99%